(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to find out how the role of the Social Service in Overcoming Exploitation of Street Children in Makassar City. This study uses a qualitative method with a descriptive type. Data collection techniques include observation, interviews and documentation. The data is analyzed through data reduction, data presentation, and drawing conclusions. The data validation technique was carried out through source triangulation, technical triangulation and time triangulation. The research results obtained show that (1) The role of the Social Service as Facilitative has facilitated RPTC (Trauma Center Shelter Homes) for PMKS. (2) The role of the Social Service as Education seeks to provide informal education in accordance with established regulations. (3) The Role of the Office of Social Affairs Social Service as a Representative cooperates with Polres/Polda, Satpol PP, BLK, TKSK and the community (4) The role of the Social Service as a Technical has special officers to collect and analyze data regarding PMKS.